If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = -4 + 4m + 5 Reorder the terms: 1 = -4 + 5 + 4m Combine like terms: -4 + 5 = 1 1 = 1 + 4m Add '-1' to each side of the equation. 1 + -1 = 1 + -1 + 4m Combine like terms: 1 + -1 = 0 0 = 1 + -1 + 4m Combine like terms: 1 + -1 = 0 0 = 0 + 4m 0 = 4m Solving 0 = 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 0 + -4m = 4m + -4m Remove the zero: -4m = 4m + -4m Combine like terms: 4m + -4m = 0 -4m = 0 Divide each side by '-4'. m = 0 Simplifying m = 0
| 4v+8=6(v+4) | | 114=39.95x | | 12x-6-6x-8=4-3x | | 5(3x-10)-5x=-15 | | 39=-3v | | 21x+3d=45 | | 7y^2-y+2=0 | | 19y-10=11y-2 | | 6.4=1.3-0.7y | | X+67+x+127=180 | | 36-7b=-3b(8b+5) | | 2y-3y+5y=42 | | 5h+4=3h+8 | | -54=9x | | 5m+4=-26 | | X^2/x-5 | | 5h+4=h+8 | | 11=x-12 | | 88+2x+62=2x+26 | | 4/(x-2)=6 | | 1.1x-3x=-34.3 | | 12-r=-8 | | 26=(5-x) | | -2(7u-2)+3u=1+2(2u-1) | | 40=2(x-4) | | -2=n+(-17) | | -5+.25c=15 | | 2x^2+3x+8=3x-10 | | 6x-1=133 | | v-(-10)=17 | | 20+8x-88=-12 | | 4s^3+12s^2-64s-192=0 |